Student perception towards the services and facilities provided by Maktab Adabi Maharani / Mohd. Iswandi Bakri - Bakri, Mohd. Iswandi (2000)
This paper presents the findings of studies conducted at Maktab Adabi Maharani, a private school located in Muar, Johor in the area of perceived quality of services and facilities provided in the school. The research project undertaken incorporated several studies of services and facilities provided by the private school. The individual study components focused on the following issues: Financial characteristics of the school and relationships to other factors. Assessment of quality of facilities provided in the private school. Students' perceptions of academic programs and their relationships to total perceptions of quality towards the school's instructors. This series of studies conducted over a period beginning in early January 2000 and culminating in April 2000, was designed to assess the perceptions of students about the quality of their school in terms of services and facilities provided. The study was conducted by using survey method. Some information were obtained from the school records, pamphlets, or any other related documents. The overall results are separated into for subsections. The first is regards to general characteristics analysis. Second section is regarding the financial factors. The third section is due to facilities analysis. Finally, the study attempts to examine the perception of students regarding instructors and aspiration factors.